MOTIVASI KONSUMEN MEMBELI KUBIS SEGAR DI PASAR PASIR GINTUNG BANDAR LAMPUNG - Paramita Wisnuwardhani; Dyah Aring Hepiana Lestari; Hurip Santoso (Lampung University, 2015)
This research aimed to analyze the perception and its related factors, motivation and its correlation to perception, the attitudes and its correlation to motivation of consumers in buying fresh cabbage. This research was conducted at Pasir Gintung Market in Bandar Lampung. Research data was collected during month of February to March 2014. The numbers of samples as many as 60 respondents were drawn by accidental sampling. Research data was analyzed by correlation analysis of Rank Spearman and by quantitative and qualitative descriptive analysis. The results showed that the perception, motivation, and attitude of consumers in buying fresh cabbage were categorized as high criteria. The internal factors (knowledge, habits, desires, needs, and income) and external factors (price, color, freshness, availability, expired time, hygiene and safety of the cabbage, convenience and service of the market) correlated to the perception of consumers in buying fresh cabbage at Pasir Gintung Market. Consumers’ perception correlated to their motivation; whereas consumers’ motivation correlated to their attitudes in buying fresh cabbage at Pasir Gintung Market. Key words: attitude, cabbage, motivation, perception